2018
DOI: 10.1186/s13068-018-1173-1
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic cultivation of Auxenochlorella protothecoides using forest biomass as a feedstock for sustainable biodiesel production

Abstract: BackgroundThe aim of this work was to establish a process for the heterotrophic growth of green microalgae using forest biomass hydrolysates. To provide a carbon source for the growth of the green microalgae, two forest biomasses (Norway spruce and silver birch) were pretreated with a hybrid organosolv-steam explosion method, resulting in inhibitor-free pretreated solids with a high cellulose content of 77.9% w/w (birch) and 72% w/w (spruce). Pretreated solids were hydrolyzed using commercial cellulolytic enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 65 publications
5
53
0
Order By: Relevance
“…Glucose is a commonly used carbon source for the heterotrophic mode of cultivation; however, it must be obtained from renewable sources to avoid the high cost associated with feedstocks [66]. Various inexpensive raw materials obtained from inedible lignocellulosic biomass from forests such birch, spruce, and beech, or agricultural residues such as rice and wheat straw, sugarcane bagasse, corn stover, waste molasses, soy whey, and industrial wastewater, have been successfully applied to support heterotrophic cultivation [69][70][71][72].…”
Section: Oleaginous Microalgaementioning
confidence: 99%
“…Glucose is a commonly used carbon source for the heterotrophic mode of cultivation; however, it must be obtained from renewable sources to avoid the high cost associated with feedstocks [66]. Various inexpensive raw materials obtained from inedible lignocellulosic biomass from forests such birch, spruce, and beech, or agricultural residues such as rice and wheat straw, sugarcane bagasse, corn stover, waste molasses, soy whey, and industrial wastewater, have been successfully applied to support heterotrophic cultivation [69][70][71][72].…”
Section: Oleaginous Microalgaementioning
confidence: 99%
“…The acid and solvent concentrations used were the same in all solid-to-liquid ratios, showing that as the solid loading increased, the amount of sulphuric acid and 50% aqueous ethanol added per gram of substrate decreased remarkably. At a solid loading of 1:2, the concentration of sulfuric acid per gram of substrate was 0.014%, a much lower value than that commonly used in the pretreatment of lignocellulosic materials when applying organosolv pretreatment [37,42,43]. Nonetheless, environmental issues are related to the production of sulphuric acid, making a search for alternative catalysts worthwhile.…”
Section: Discussionmentioning
confidence: 98%
“…A review on the use of organosolv pretreatment for the delignification of lignocellulosic materials in the last two years showed that an S/L ratio of 1:10 predominated [8]. Exceptions include the works carried out by Matsakas et al [36] using silver birch wood chips, by Patel et al [37] using Norway spruce, and by Yuan et al [38] using corn stover, wherein an S/L ratio of 1:2 was used. Research works in the literature reported lignin-rich fractions containing >90% lignin [8] achieved via different organosolv pretreatment strategies, namely HCl-catalyzed tetrahydro-2-furanmethanol pretreatment of eucalyptus [39], auto-catalyzed ethanol pretreatment of Eucalyptus nitens bark [40], and oxalic acid-catalyzed glycerol pretreatment of sugarcane trash [41].…”
Section: Discussionmentioning
confidence: 99%
“…The triterpene squalene is an antioxidant and an important biosynthetic precursor to all human steroids [180]. In cosmetics, it is better applied in its saturated form obtained after hydrogenation, named squalane.…”
Section: Algae and Their Compounds As Humectants And Moisturizersmentioning
confidence: 99%